(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current study aims to know what human capital is and to determine the impact of human capital efficiency in achieving total asset turnover rates in Iraqi joint-stock companies. The analytical and statistical approach has been relied on in analyzing the companies’ data, the study sample using the Eviews-9 program. In order to answer the questions of the current study and achieve its objectives, a sample of industrial companies participating in the study was tested, depending on the data available in the Iraq Stock Exchange for the period extending from (2011-2019), as the sample included (8) listed industrial companies. As the current research found a positive impact relationship for human capital efficiency (HCE) on the total asset turnover rate in the industrial companies sample of the study, as the efficiency of the human element affects the rates of asset turnover by raising operational performance and improving operations and thus the repeated use of assets and increase their turnover rates.